2001
DOI: 10.1063/1.1415408
|View full text |Cite
|
Sign up to set email alerts
|

Emission uniformity and emission area of explosive field emission cathodes

Abstract: Explosive field emission cathodes have been used extensively in high power microwave tubes. These cathodes emit electrons without the use of cathode heaters. Recently, some theoretical and simulation work has been performed to gain further understanding of the physics of these cathodes. The purpose of this letter is to provide the experimental background and justification for the theoretical work. The general idea of how explosive field emission cathodes operate is that plasma is rapidly formed, which provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…While these efforts have been focused primarily on basic R&D, spin-offs of this work have already shown themselves in confirmation of these 2-D effects from in-house experimental cathode tests as well as from actual HPM device results. Specifically, these 2-D simulations predict that identical total currents can be drawn from cathodes of the same bulk area even though they may vary significantly in micro-geometry; such an effect was confirmed through in-house experiments [10][11][12][13] that used a variety of cathode materials and micro-geometries yet observed the same total current in each case. In addition, this work has shown that extremely small changes in local electric field near the cathode edge can drastically alter the current density being drawn from that edge; one such example is the "field-shaper" cathode that helped moderate high current-density flares inside AFRL's Magnetically Insulated Line Oscillator (MILO) HPM device [14][15] thereby resulting in improvements of pulse duration as well as reproducibility.…”
Section: Space Charge-limited Flow Simulationsmentioning
confidence: 74%
“…While these efforts have been focused primarily on basic R&D, spin-offs of this work have already shown themselves in confirmation of these 2-D effects from in-house experimental cathode tests as well as from actual HPM device results. Specifically, these 2-D simulations predict that identical total currents can be drawn from cathodes of the same bulk area even though they may vary significantly in micro-geometry; such an effect was confirmed through in-house experiments [10][11][12][13] that used a variety of cathode materials and micro-geometries yet observed the same total current in each case. In addition, this work has shown that extremely small changes in local electric field near the cathode edge can drastically alter the current density being drawn from that edge; one such example is the "field-shaper" cathode that helped moderate high current-density flares inside AFRL's Magnetically Insulated Line Oscillator (MILO) HPM device [14][15] thereby resulting in improvements of pulse duration as well as reproducibility.…”
Section: Space Charge-limited Flow Simulationsmentioning
confidence: 74%
“…These cathodes consist of an array of carbon fibers pyrolytically bonded to a carbon substrate or attached to a metal substrate using electrically conductive epoxy, or carbon fibers are bundled into bunches each containing ∼10 3 microfibers and posi-* Corresponding author. tioned on the cathode substrate [13,14]. In spite of recent research breakthroughs, the long-lived, low work-function, uniformly emitting, low emittance, high current density cathodes are still one of the remaining challenges in this area.…”
Section: Introductionmentioning
confidence: 98%
“…It was observed that a large portion of cathode area may not be taking part in the EEM process [15], [16]. Perveance data have been used to calculate the initial emission area and plasma expansion velocity.…”
Section: Introductionmentioning
confidence: 99%